Türkiye’de 1980-2024 yılları arasında gelir dağılımının görünümü ve gelir dağılımına etki eden faktörlerin incelenmesi - Budak, Selin (My University, 2025)
Türkiye’de 1980-2024 yılları arasında gelir dağılımının görünümü ve gelir dağılımına etki eden faktörlerin incelenmesi Bir ülkedeki adaletsiz gelir dağılımı, çeşitli yollardan ülke refahını olumsuz etkileyerek yoksulluk olgusunu oluşturmaktadır. En yüksek gelir grubuna mensup nüfus diliminin, en düşük gelir grubuna mensup nüfus dilimi ile oluşan gelir farkının büyümesi, sağlık,beslenme, eğitim gibi sorunları da beraberinde getirerek toplumsal refahı bozmaktadır.Çalışmada Türkiye’de 1980-2024 yılları arasında gelir dağılımına dair gelişmeler, veriler ışığında anlatılmıştır. Gelir dağılımını etkileyen faktör ve politikaların, gelir dağılımını hangi kanallardan etkileyebileceği izah edilmiş ve bu faktörlerin Türkiye’deki görünümü ortaya konulmuştur. Gelir dağılımını etkileyen yapısal faktörler; ekonomik büyüme, işsizlik, ekonomik krizler, enflasyon, kayıt dışı ekonomi, nüfus ve göç başlıkları altında, politikalar ise para, maliye, dış ticaret, eğitim, tarım, ücret, sosyal güvenlik politikaları başlıkları altında değerlendirilmiştir. Gelir dağılımı sorununu bir bütün olarak görmek amacıyla yazılan her bir başlığın gelir dağılımı ile ilişkisi saptanmıştır. Türkiye’de 2000’li yılların başından bu yana mutlak yoksulluk oranlarında nispi bir azalma görülse de gini katsayısının 1980’den günümüze değin 0,40 sularından geriye gitmediği ve bu katsayının OECD ülkelerinin ortalamasının üzerinde olduğu sonucuna varılmıştır. Dolayısıyla Türkiye’nin esas sorununun mutlak yoksulluktan ziyade gelir eşitsizliği olduğu ve bu sorunun toplumsal barış için büyüme, nüfus, kayıt dışı ekonomi, işsizlik,enflasyon, para ve maliye politikaları, eğitim politikaları tarım politikaları, dış ticaret politikaları, ücret ve sosyal güvenlik politikaları bağlamında değerlendirilip sorunların kaynağına inilerek bütüncül bir bakış açısıyla çözülmesi gerekli görülmektedir.

The outlook of income distribution in Turkey between 1980-2024 and an examination of the factors affecting income distrıbution Unfair income distribution in a country negatively impacts national welfare in various ways, creating the phenomenon of poverty. The widening income gap between the highest-income segment and the lowest-income segment not only creates poverty but also leads to problems such as health, nutrition, and education, disrupting social well-being.The fundamental question of this study is whether income equity and poverty have existed in Turkey since 1980. To answer this question, the factors and policies affecting income distribution, along with the channels through which they can influence it, are explained, and the outlook for these factors in Turkey is presented. Structural factors affecting income distribution are evaluated under the headings of economic growth, unemployment, economic crises, inflation, the informal economy, population, and migration, while policies are evaluated under the headings of monetary, fiscal, foreign trade, education, agriculture, wage, and social security policies. To provide a holistic view of the income distribution problem, the relationship between each heading and income distribution is determined. Although absolute poverty rates have decreased relatively in Turkey since the early 2000s, the Gini coefficient has remained around 0.40 since 1980. There has been no significant change in the income distribution picture between the years. While the share of the lowest-income group has occasionally increased, the gap between this group and the highest-income group is clear, with a larger share of the income earned by a smaller segment. Therefore, it has been concluded that Turkey's fundamental problem is income inequality rather than absolute poverty. This problem must be evaluated within the context of growth, population, the informal economy, unemployment, inflation, monetary policies, fiscal policies, education policies, agricultural policies, foreign trade policies, wage and social security policies, and resolved from a holistic perspective by addressing the root causes of the problems for social peace.
The outlook of income distribution in Turkey between 1980-2024 and an examination of the factors affecting income distrıbution
Keywords: Economic conditions; Ekonomik durum; Gelir dağılımı; Gini Coefficient; Gini Katsayısı Income Distribution; Income distribution; Poverty; Turkey; Türkiye; Yoksulluk